The impact of cognitive bias about infectious diseases on social well-being - Pestow, Radomir (Frontiers in Epidemiology, 2024)
We investigate the relationship between bias, that is, cognitive distortions about the severity of infectious disease and social well-being. First, we establish empirically the existence of bias and analyze some of its causes; specifically, during the COVID-19 pandemic. Second, we derive an integrated economic-epidemiological differential equation model from an agent-based model that combines myopic rational choice with infectious disease dynamics. Third, we characterize axiomatically a model of an ethical, impartial, eudaemonistic and individualist observer. We prove that such an observer evaluates the state of society (social welfare or well-being) according to the utilitarian principle. Fourth, we show numerically that while increased risk-perception indeed improves epidemiological outcomes such as peak of infections and total incidence, the impact on social well-being is ambiguous. This result urges to look beyond cases and deaths. Finally, we point out three possible future research directions and highlight some critical issues that arise in the normative direction.